Does Sequence of Graft Tensioning Affect Outcomes in Combined Anterior and Posterior Cruciate Ligament Reconstructions?. Issue 1 (January 2015) - Kim, Sung‐Jae; Kim, Sung‐Hwan; Jung, Min; Kim, Jong‐Min; Lee, Se‐Won
Abstract: Background: Controversy persists regarding the protocol for tensioning and securing the grafts in one‐stage reconstruction of combined anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) injuries. Many authors have reported stability examinations and functional results after reconstruction for this relatively rare injury, and the best sequence for tensioning the grafts is not known. Questions/purposes: We sought to determine (1) if there are differences in postoperative anteroposterior stability in a protocol of simultaneous tensioning of both grafts and ACL‐first fixation compared with a protocol of tensioning and fixation of the PCL first in one‐stage reconstruction of combined ACL/PCL injuries; and (2) if there is a difference in postoperative functional outcome scores between the two protocols. Methods: Between 2001 and 2011, 29 patients underwent one‐stage reconstruction of combined ACL and PCL injuries (the majority with medial collateral ligament [MCL] injuries, posterolateral corner [PLC] injuries, or both, in addition), of whom three patients (10%) were lost to followup before 2 years, and one patient was excluded based on predefined criteria, leaving a total of 25 patients (86%) for retrospective analysis in this report. Fourteen patients underwent one‐stage reconstruction of these injuries with tensioning and fixation of the PCL graft first (PCL‐first group), and 11 later patients underwent one‐stage reconstruction of combined ACL/PCL injuries with simultaneous tensioning of both grafts and fixation of the ACL graft first (simultaneous‐tensioning group). During the period in question, the technique used in the PCL‐first group was used exclusively for these injuries between August 2001 and August 2008 and that used in the simultaneous‐tensioning group was used between September 2008 and August 2011; there was no overlap between groups. The groups were similar in terms of demographics and length of followup. Each patient was assessed for associated injuries, preoperative and postoperative knee stability with anteroposterior stress radiographs, and was evaluated with the Lysholm knee score and International Knee Documentation Committee (IKDC) subjective and objective grading at the last followup after surgery. Results: At the last followup evaluation, patients treated with simultaneous tensioning and ACL‐first fixation showed less instability on side‐to‐side difference of posterior stress radiography (5 ± 1 mm in the simultaneous‐tensioning group versus 6 ± 1 mm in the PCL‐first group; effect size, 1.2; 95% confidence interval [CI], 0.5‐2.3; p = 0.011), but with the numbers available, no difference on anterior stress radiography (3 ± 0.4 mm in the simultaneous‐tensioning group versus 3 ± 0.5 mm in PCL‐first group; effect size, 0.4; 95% CI, −0.2 to 0.5; p = 443). The simultaneous‐tensioning group also had higher Lysholm knee scores (87 ± 5 in the simultaneous‐tensioning group versus 80 ± 4 in the PCL‐first group; effect size, 1.8; 95% CI, −10.9 to −2.7; p = 0.001), IKDC subjective scores (68 ± 3 in the simultaneous‐tensioning group versus 58 ± 3 in the PCL‐first group; effect size, 3.4; 95% CI, −14.2 to −8.6; p < 0.001), and IKDC objective grades (p = 0.037). Conclusions: In one‐stage reconstruction of combined ACL and PCL injuries, a protocol of simultaneous tensioning both grafts and fixing the ACL graft first may be worth consideration. Arthroscopic reduction landmarks may prove helpful in this technique but require further validation. Level of Evidence: Level III, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.